The role of loyalty in private label consumer based brand equity - Fernando, João Tavares (2020)
Private label products have become so appealing that not even big retail chains can dismiss them. Initially seen as cheap alternatives, they now compete with premium national brand products, since consumers perceive them as legitimate and trustworthy brands. It’s imperative that brand equity dimensions are seen through the light of private labels. The main focus of this thesis is to better understand the relationship between private label loyalty and consumer based brand equity, improving and applying previous scales and frameworks to a new universe. This framework relates the different dimensions of brand equity with brand equity itself, also looking at the hierarchical relationship between them. It takes into account the brand equity dimensions derived from private label brand research and their influence on the brand equity based dimensions. Regarding conclusions, in order to increase brand awareness, retailers should invest in strategies such as store taste tests, comparisons with other brands, samples or coupons, or invest in extrinsic cues like package design, labeling and branding strategies. Low product risk is essential to foster product quality, reliability and consistency. Only a risk-free product will be able to grow, allowing it to become a familiar item in the consumer’s basket. The most relevant factors in influencing the purchase of private label goods are brand familiarity, perceived value and perceived risk of goods. In the end, it’s seen the influence that perceived value has on the whole process, impacting private label antecedents, CBBE antecedents and brand loyalty itself.